E-learning in a Jordanian higher education institution - Alnemrat, Areen; Aldamen, Hesham; Al-Deaibes, Mutasim; Alsharefeen, Rami (Frontiers in Psychology, 2023)
This study seeks to understand the current level of e-learning and to investigate the challenges to the successful implementation of e-learning at a major Jordanian higher education institution from the perspectives of faculty members. Analyses of emailed survey data from 157 faculty members showed that the level of faculty knowledge of e-learning was good (M = 3.049) on the 4-point Likert scale. The usage of e-learning by the faculty members was often (M = 3.640) on the 5-point Likert scale. Ratings of the policy and support barriers indicated that Yarmouk University faculty members benefit from the technical support that their departments offer to implement e-learning, but the overall responses to the policy and support barriers were undecided (M = 3.567). Also, overall Yarmouk University faculty members’ responses to the infrastructure and resources barriers were undecided (3.482). Attitude item responses showed that Yarmouk University faculty members have positive attitudes and a willingness to implement e-learning in their teaching (M = 3.913). Also, responses showed a degree of satisfaction of faculty members with the development plans and strategies associated with e-learning (M = 3.668). They showed that they did not have obstacles in preparation and development and that they benefited from their plans and strategies. The results showed that there were no differences between males and females on e-learning knowledge, usage, and barriers.